The effect of earnings management on investment efficiency moderated by ceo remuneration - Edi, Edi; Franita, Franita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this research is to analysis the effect of earnings management on investment efficiency, and also included remuneration CEO as moderating variable. The object of this study is manufacturing company listed on Indonesia Stock Exchanges from 2017 to 2020. The research data are processed through the statistical application of Statistical Product and Service Solutions (SPSS) 25 and Smart PLS (Partial Least Square) 3.2.9. The research results found that earnings management has no significant effect on investment efficiency. Moreover, research results also found that CEO remuneration can moderate the relationship between earnings management and investment efficiency. The findings of this study are beneficial for corporate governance in making investment decisions as well as protecting investors by reflecting the transparency of financial statements to avoid managerial opportunistic. A strong mechanism for management is important in preventing opportunism, due to certain earnings management motivations will be carried out in order to increase the amount of compensation incentives. The novelty of this research provides new insight into how CEO remuneration moderates the relationship between earnings management and investment efficiency.